A Preconditioned 3-D Multi-Region Fast Multipole Solver for Seismic Wave Propagation in Complex Geometries (Communications in Computational Physics, 2020)
The analysis of seismic wave propagation and amplification in complex geological structures requires efficient numerical methods. In this article, following upon recent studies devoted to the formulation, implementation and evaluation of 3D single- and multi-region elastodynamic fast multipole boundary element methods(FM-BEMs), a simple preconditioning strategy is proposed. Its efficiency is demonstrated on both the single- and multi-region versions using benchmark examples (scattering of plane waves by canyons and basins). Finally, the preconditioned FM-BEMis applied to the scattering of plane seismic waves in an actual configuration (alpinebasin of Grenoble, France), for which the high velocity contrast is seen to significantlyaffect the overall efficiency of the multi-region FM-BEM.